What factors drive gender differences in the body mass index? Evidence from Turkish adults - ÇAĞLAYAN AKAY, EBRU (My University, 2023)
In recent years, studies show that obesity has become an important health condition, especially among adults. The first aim of this study is to examine socio-demographic and behavioural factors on body mass index distribution of male and female adults over 20 years old in Turkey. The second aim is to determine the body mass index disparity by gender and the socio-demographic and behavioural factors that might wider or narrow it. This study adopts unconditional quantile regression and decomposition methods, and the data set covers the Turkish Health Surveys for 2014, 2016, and 2019. The findings document that high level of body mass index are associated with being married, aging, and physical inactivity. Interestingly, employment status has different contributions on the body mass index of males and females. The results also claim a body mass index gap among males and females as a result of differences in some potential socio-demographic and behavioural factors, and the gap gets higher at the upper and lower quantiles of BMI distribution. This study may provide a clear understanding for policymakers on how to design efficacious obesity policies considering the differences in the effect of socio-demographic and behavioural factors on the distribution of body mass index across females and males. The results suggest that the Ministry of Health should specifically target different groups for males and females and should reduce the differences in socio-demographic and behavioural determinants between females and males to prevent and reduce obesity prevalence in Turkey.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Demografi; Social Sciences and Humanities; Sociology; Demography; DEMOGRAFİ; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); KAMU, ÇEVRE VE İŞ SAĞLIĞI; SOSYAL BİLİMLER, BİYOMEDİKSEL; DEMOGRAPHY; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, BIOMEDICAL; İş Sağlığı ve Terapisi; Yaşam Boyu ve Yaşam Boyu Çalışmaları; Güvenlik Araştırması; Sağlık (sosyal bilimler); Genel Sosyal Bilimler; Halk, Çevre ve İş Sağlığı; Epidemiyoloji; Sağlık Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Occupational Therapy; Life-span and Life-course Studies; Safety Research; Health (social science); General Social Sciences; Public Health, Environmental and Occupational Health; Epidemiology; Health Sciences; Social Sciences & Humanities; Body mass index; socio-demographic factors; behavioural determinants; unconditional quantile regression; decomposition; Turkey; SOCIOECONOMIC-STATUS; PHYSICAL-ACTIVITY; OBESITY; PREVALENCE; REGRESSION; OVERWEIGHT; CONSUMPTION